2021
DOI: 10.1371/journal.pone.0250601
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and physical characteristics distinguishing adult Patagonian lamprey, Geotria macrostoma from the pouched lamprey, Geotria australis

Abstract: The pouched lamprey, Geotria australis Gray, 1851, has long been considered monotypic in the Geotriidae family with a wide southern temperate distribution across Australasia and South America. Recent studies have provided molecular and morphological evidence for a second Geotria species in South America; Geotria macrostoma (Burmeister, 1868). The aim of this study was to determine morphometric and physical characteristics of adult G. macrostoma that further differentiate this re-instated species of Geotriidae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 33 publications
(116 reference statements)
5
24
0
Order By: Relevance
“…Crucially, the examination of numerous G. australis from Australasia and Chile and G. macrostoma from Argentina shows that the TLL of these lampreys possesses three prominent cusps at the completion of metamorphosis and up to the commencement of the upstream spawning migration and thus implicitly including the marine feeding phase (de Buen, 1961; Hubbs & Potter, 1971; Potter et al ., 1980; Neira, 1984; figure 6b,f in Baker et al ., 2021, the former reproduced here in Figure 1a,c). The possession of a large central cusp on the TLL, as well as the two large cusps to either side, is crucial for the feeding process in Geotria .…”
Section: Species Catalogue/reference Locality Stage Number Of Cusps A...mentioning
confidence: 64%
See 4 more Smart Citations
“…Crucially, the examination of numerous G. australis from Australasia and Chile and G. macrostoma from Argentina shows that the TLL of these lampreys possesses three prominent cusps at the completion of metamorphosis and up to the commencement of the upstream spawning migration and thus implicitly including the marine feeding phase (de Buen, 1961; Hubbs & Potter, 1971; Potter et al ., 1980; Neira, 1984; figure 6b,f in Baker et al ., 2021, the former reproduced here in Figure 1a,c). The possession of a large central cusp on the TLL, as well as the two large cusps to either side, is crucial for the feeding process in Geotria .…”
Section: Species Catalogue/reference Locality Stage Number Of Cusps A...mentioning
confidence: 64%
“…In some instances, the authors have observed an even earlier transition from three to two cusps on the TLL. Early upstream migrants of G. australis from the Waikawa River (46.59° S, 169.14° E), New Zealand (figure 6e in Baker et al ., 2021, reproduced here in Figure 1b), and the lower Murray River, Australia (35.53° S, 138.81° E), and early and late upstream migrants of G. macrostoma from the Chubut (43.45° S, 65.91° W) and Santa Cruz rivers (50.05° S, 69.01° W), Argentina (figure 6d in Baker et al ., 2021; Figure 1d), already show a bicuspid state, indicating that reduction or loss of the middle cusp may occur just before entering the fresh water, at the beginning of the spawning run. A reduction in the size of the middle cusp on the TLL or replacement of the tricuspid TLL by a bicuspid TLL has already been observed in upstream migrants of G. australis from Australia, New Zealand and Chile by Maskell (1929) and De Buen (1961) and in G. macrostoma from Argentina and Islas Georgias del Sur (South Georgia Island) by Lahille (1915) and Potter et al .…”
Section: Species Catalogue/reference Locality Stage Number Of Cusps A...mentioning
confidence: 82%
See 3 more Smart Citations